Efficacy and safety of Tripterygium wilfordii multiglucoside for idiopathic membranous nephropathy: a systematic review with bayesian meta-analysis - Wang, Hongyun; Liu, Hongyan; Xue, Xue; Wang, Qiong; Yuan, Jun (Frontiers in Pharmacology, 2023)
Background: Currently, the optimal therapy plan for idiopathic membranous nephropathy (IMN) remains controversial as there has been no comprehensive and systematic comparison of therapy plans for IMN. Therefore, in this study, a Bayesian meta-analysis was used to systematically evaluate the clinical efficacy and safety of various intervention plans involving traditional Chinese medicine TWM in the treatment of IMN. Methods: An electronic search in 7 databases was conducted from their inception to August 2022 for all published randomized controlled trials (RCTs) of various intervention plans for IMN. Network meta-analysis (NMA) was performed by using software R, and the surface under the cumulative ranking area (SUCRA) probability curve was plotted for each outcome indicator to rank the efficacy and safety of different intervention plans. Results: A total of 30 RCTs were included, involving 13 interventions. The results showed that (1) in terms of total remission (TR), ①GC+CNI+ TWM was the best effective among all plans, and the addition and subtraction plan of CNI+TWM was the best effective for IMN; ② All plans involving TWM were more effective than GG; ③ Among monotherapy plans for IMN, TWM was more effective distinctly than GC, while TWM and CNI were similarly effective; ④ Among multidrug therapy plans for IMN, the addition of TWM to previously established therapy plans made the original plans more effective; ⑤The efficacy of combining TWM with other plans was superior to that of TWM alone. (2) In terms of lowering 24h-UTP, GC+TWM was the best effective and more effective than TWM. (3) In terms of safety, there was no statistically significant difference between all groups. However, CNI+TWM was the safest. No serious adverse events (AEs) occurred in all the included studies. Conclusion: The addition of TWM may be beneficial to patients with IMN. It may enhance the efficacy of previously established treatment protocols without leading to additional safety risks. In particular, GC+CNI+TWM, GC+TWM, and CNI+TWM with better efficacy and higher safety can be preferred in clinical decision-making as the therapy plans for IMN.